2020
DOI: 10.1186/s40662-019-0171-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy outcomes of the Xen45 Gel Stent use for refractory glaucoma: a surgery series from surgeon trainees at a tertiary teaching hospital

Abstract: Background: To study the effect of an ab interno gelatin stent (XEN45 Gel Stent, Allergan Inc., Irvine, California, USA) on intraocular pressure (IOP) as placed by glaucoma fellowship trainees in eyes with refractory glaucoma. Methods: A prospective noncomparative study at a tertiary training center on 28 unique eyes undergoing ab interno gelatin stent implantation by glaucoma fellowship trainees. Data was collected at baseline and postoperatively at day 1, week 1, and months 1, 3, 5, and 12. Primary outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Such reports on the IOP reducing efficacy rates for adverse effects and visual recovery have been published for XEN45 9 , 10 , 11 and also for the PreserFlo Microshunt 12 . According to the literature, XEN45 was successfully applied to various forms of glaucoma, resulting in IOP readings comparable to ours 13 , 14 , 15 , 16 . However, there are fewer published studies on the PreserFlo Microshunt (industry-initiated trials), as this product has only been on the market under the current name since 2016 compared to XEN45 (since 2014).…”
Section: Discussionsupporting
confidence: 59%
“…Such reports on the IOP reducing efficacy rates for adverse effects and visual recovery have been published for XEN45 9 , 10 , 11 and also for the PreserFlo Microshunt 12 . According to the literature, XEN45 was successfully applied to various forms of glaucoma, resulting in IOP readings comparable to ours 13 , 14 , 15 , 16 . However, there are fewer published studies on the PreserFlo Microshunt (industry-initiated trials), as this product has only been on the market under the current name since 2016 compared to XEN45 (since 2014).…”
Section: Discussionsupporting
confidence: 59%
“…A number of studies have examined ab interno XEN Gel Stent implantation in mixed POAG populations and found mean IOP reductions ranging from 28 to 42.1% with postoperative IOPs ranging from 12 to 15 mmHg. 18 , 21 , 22 , 23 , 24 , 37 , 38 , 39 , 40 , 41 Direct comparison of ab interno XEN Gel Stent implantation with trabeculectomy in POAG patients found no difference in the rates of surgical success or reduction in IOP lowering medications. 24 , 39 , 42 , 43 While one study found that trabeculectomy resulted in lower postoperative IOPs, 39 others found no difference.…”
Section: Discussionmentioning
confidence: 97%
“…The efficacy of the XEN implant was demonstrated in intermediate and incipient glaucoma [ 14 , 15 ]. However, only few studies have evaluated the efficacy of XEN implants in OUG [ 16 18 ], and the longest follow-up period in these studies was 12 months. Therefore, this study aimed to retrospectively evaluate the efficacy of XEN implantation in 72 patients with OUG during a long-term follow-up period.…”
Section: Introductionmentioning
confidence: 99%